Biotechnology and bioinformatics : advances and applications for bioenergy, bioremediation, and biopharmaceutical research - Thangadurai, Devarajan, 1976-; Sangeetha, Jeyabalan (Apple Academic Press, 2014)
Reflecting the interdisciplinary nature of biotechnology, this book covers the role of targeted delivery of polymeric nanodrugs to cancer cells, microbial detoxifying enzymes in bioremediation and bacterial plasmids in antimicrobial resistance. It addresses modern trends such as pharmacogenomics, evaluation of gene expression, recombinant proteins from methylotrophic yeast, identification of novel fermentation inhibitors of bioethanol production, and polyhydroxyalkanoate based biomaterials. The book highlights the practical utility of biotechnology and bioinformatics for bioenergy, producti.